2018
DOI: 10.3390/w10070843
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multiple Typhoons on Severe Floods in the Mid-Latitude Region (Hokkaido)

Abstract: Mid-latitude regions in the North Pacific are generally vulnerable to climatological disasters and are possibly more sensitive to future climate changes. Severe flood disasters struck Hokkaido in August 2016 because of the multiple, continuous typhoons that struck the island. We evaluated the effect of these typhoons on floods and changes in future floods using a distributed hydrological model in a watershed located in eastern Hokkaido. We conducted two numerical examinations: a simulation with a major typhoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Such analyses relevant to extremes are possible using the large ensembles without statistical hypothesis. Similar results were obtained in different river basins in Japan and other countries: the Nagara river basin by Harada et al (2018), the Hokkaido region by Kimura et al (2018) and (Masuya et al 2018), and Indochinese Peninsula by Hanittinan et al (2018).…”
Section: Assessment Of Risks Due To Heavy Precipitation and River Flosupporting
confidence: 83%
“…Such analyses relevant to extremes are possible using the large ensembles without statistical hypothesis. Similar results were obtained in different river basins in Japan and other countries: the Nagara river basin by Harada et al (2018), the Hokkaido region by Kimura et al (2018) and (Masuya et al 2018), and Indochinese Peninsula by Hanittinan et al (2018).…”
Section: Assessment Of Risks Due To Heavy Precipitation and River Flosupporting
confidence: 83%
“…According to our previous study [15], the soil had exhausted its water capacity in the southwest portion of the TR watershed before the fourth typhoon and, as a result, the severe flood disaster occurred during the fourth typhoon's approach toward Hokkaido. The agricultural damage areas at the Nakajima Bridge, Rrutanjyoryu, and Minamisatsunai Stations calculated in the current flood simulation were 3-10 km 2 along the tributaries where overflow events occurred, but not at Moiwa Station.…”
Section: Discussionmentioning
confidence: 99%
“…In other research related to the August 2016 disaster, Kimura et al [15] showed that with a hydrological model and observed rainfall data, the effect of the preceding three typhoons on flood disasters was crucial as the water capacity in soil in the west side of the TR watershed was exceeded before the fourth typhoon approached, which then made the flood disaster worse by producing massive rainfalls. However, this previous study was limited to understanding the future trend because there is no future rainfall data based on climate change scenarios as an extended investigation of the August 2016 disaster.…”
Section: Integrated Flood Analysis System (Ifas)mentioning
confidence: 99%
See 2 more Smart Citations